Strategies for selection of thermo-chemical processes for the valorisation of biomass. (December 2016) - Singh, Rawel; Krishna, Bhavya B.; Mishra, Garima; Kumar, Jitendra; Bhaskar, Thallada
Abstract: Research on biomass conversion has been gaining a lot of interest as biomass is renewable and sustainable in nature. Products from biomass can be obtained by different methods amongst which thermo-chemical route has a very high potential. Biomass is generally available in a localised manner in varying quantities and qualities throughout the year and hence, region specific technologies have to be developed considering the end user requirement. Pyrolysis is a very versatile technique with the above considerations. The process parameters can be tweaked to necessity to produce more bio-oil or bio-char. Thermogravimetric analysis is essential for understanding the decomposition behaviour of the feedstock before the lab scale pyrolysis is carried out. Pyrolysis using several regional feedstocks has been carried out under nitrogen and hydrogen atmosphere and different biomass feedstocks were also liquefied using sub/supercritical solvents. This review aims to provide a comparison of the results obtained using various processes. This helps in the decentralised processing of biomass (dry biomass using pyrolysis and wet biomass by hydrothermal liquefaction) to produce bio-crude which can be upgraded to produce fuels/chemicals/petrochemical feedstocks in an environmental friendly manner. Highlights: Pyrolysis products vary with differences in operating parameters. Diversified biomass can be utilized with multiple conversion processes. Slow pyrolysis bio-oil and bio-char can be produced in decentralised systems. Hydrothermal liquefaction is best suited for wet biomass. Integration of different processes yields high economic benefits.